Poglądy dr. Wiktora Skarżyńskiego, posła do parlamentu, filozofa - przedstawiciela nurtu konserwatywnego - na aktywność społeczno-zawodową kobiet w Wielkopolsce w drugiej połowie XIX wieku = Views by dr Wiktor Skarżyński, a deputy to Parliament, a philosopher - a representative of the conservative movement - on social and professional women's activity in Wielkopolska in the second half of the 19th century - Wyder, Grażyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the second half of the 19th century, as a result of complex social, legal and economic determinants, there grew the interest in the position of women in many spheres of life. Wielkopolska was not an exception although the Kulturkampf policy had assigned to women an important role of guards of the national identity and Polish tradition.
Keywords: Skarżyński, Wiktor (1850-1910); kobieta; Wielkopolska - historia - 19 w.